The Relations between Television Exposure and Executive Function in Chinese Preschoolers: The Moderated Role of Parental Mediation Behaviors - Yang, Xiaohui; Chen, Zhe; Wang, Zhenhong; Zhu, Liqi (Frontiers in Psychology, 2017)
The present study examined the relations between preschoolers’ television exposure and executive functions (EF). One hundred and nineteen 3- to 6-year-old children and their parents participated. Parents filled in a questionnaire regarding children’s television viewing time, television content and parental mediation behaviors about their child’s television viewing. The children were asked to finish six EF tasks, including the backward digit span task, the spatial span task, the boy-girl Stroop, the Simon task, the flanker task and the Tower of Hanoi task that assessed working memory, inhibition and planning respectively. Children’s vocabulary was tested using Peabody Picture Vocabulary Test, and included as control variables in addition to socioeconomic status of the participated families. The results showed that television viewing time and child-directed educational programs were positively associated with EF. In addition, television content fully mediated the effect of television viewing time on EF and parental restrictive approach strategies moderated the effect of television viewing time on EF.